2016
DOI: 10.1186/s12885-016-2335-9
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative chemoradiation with paclitaxel-carboplatin or with fluorouracil-oxaliplatin—folinic acid (FOLFOX) for resectable esophageal and junctional cancer: the PROTECT-1402, randomized phase 2 trial

Abstract: BackgroundOften curative treatment for locally advanced resectable esophageal or gastro-esophageal junctional cancer consists of concurrent neoadjuvant radiotherapy and chemotherapy followed by surgery. Currently, one of the most commonly used chemotherapy regimens in this setting is a combination of a fluoropyrimidin and of a platinum analogue. Due to the promising results of the recent CROSS trial, another regimen combining paclitaxel and carboplatin is also widely used by European and American centers. No c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 18 publications
0
26
1
1
Order By: Relevance
“…The NEOSCOPE study investigates whether induction chemotherapy followed by either oxaliplatin/capecitabine or paclitaxel/carboplatin, both combined with 45 Gy radiation, is superior as preoperative regimen in pathological complete response of resectable esophageal adenocarcinoma . Finally, the PROTECT‐1402 study compares three cycles of FOLFOX combined with concurrent radiotherapy (41.4 Gy) or carboplatin and paclitaxel with the same radiation regimen for esophageal and junctional cancer . An overview of these studies (including http://ClinicalTrials.gov identifiers) is presented in Table .…”
Section: Perioperative Treatment For Locally Advanced Esophageal Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The NEOSCOPE study investigates whether induction chemotherapy followed by either oxaliplatin/capecitabine or paclitaxel/carboplatin, both combined with 45 Gy radiation, is superior as preoperative regimen in pathological complete response of resectable esophageal adenocarcinoma . Finally, the PROTECT‐1402 study compares three cycles of FOLFOX combined with concurrent radiotherapy (41.4 Gy) or carboplatin and paclitaxel with the same radiation regimen for esophageal and junctional cancer . An overview of these studies (including http://ClinicalTrials.gov identifiers) is presented in Table .…”
Section: Perioperative Treatment For Locally Advanced Esophageal Cancermentioning
confidence: 99%
“…40 Finally, the PROTECT-1402 study compares three cycles of FOLFOX combined with concurrent radiotherapy (41.4 Gy) or carboplatin and paclitaxel with the same radiation regimen for esophageal and junctional cancer. 41 An overview of these studies (including ClinicalTrials.gov identifiers) is presented in Table 1.…”
Section: Perioperative Treatment For Locally Advanced Esophageal Cancermentioning
confidence: 99%
“…In the setting of definitive CRT, the PRODIGE5/ACCORD17 trial showed that the use of oxaliplatin is safer and more convenient, with fewer cases of sudden death, than cisplatin . The PROTECT trial is an ongoing randomized phase II trial comparing two NACRT regimens (CROSS vs FOLFOX) in resectable esophageal and EGJ cancers of SCC or AC …”
Section: Current Worldwide Trendsmentioning
confidence: 99%
“…It is a "pick a winner" design based on pCR,, with 38 patients with esophageal or junctional adenocarcinoma (AEG type I/II; ≥T3±≥N1) per treatment arm, the trial will be used to define the optimal regimen for a future phase III trial comparing neoadjuvant chemotherapy. Similarly, the PROTECT-1402 French trial (NCT02359968) is a phase II trial which will randomise 106 patients with stage II or III esophageal adenocarcinoma or squamous cell carcinoma to one of two neoadjuvant chemotherapy regimens with standard concurrent 41.4 Gy radiation (27). The chemo regimens are 3 cycles of FOLFOX or carboplatin/ paclitaxel.…”
Section: Key Current Questions and Active Trialsmentioning
confidence: 99%